KEPUTUSAN MEMBELI DI TOKO BAITUL MUSLIM AS-SIDIQ YOGYAKARTA (Analisis Segmen Pasar Demografis, Psikografis dan Benefit) - majidah, Siti (Universitas Darrussalam Gontor, 2014)
Muslim clothes have become the prime need (dharuriyyat) in muslim society. It is as ordered by Allah SWT in Al-Qurâan and As-Sunnah. However, there are still many muslims who buy the muslim clothes not for trend rather than practicing their religious teachings. In order to answer that doubt, the researcher initiates to do a research in the decision to buy at Baitul Muslim As-Sidiq store at Yogyakarta. This research aims to analyze demographic, benefit (maslahah) and psychographic market shareand its influence to the decision to buy at Baitul Muslim As-Sidiq 2012. Furthermore, this research aims to analyze and know the difference of the proportion of bought-product types based on psychographic and benefit (maslahah) market share. This research uses field research method with the determination of research object by descriptive analysis method which gives the description of research object through data sample that represent needed population. The result from this research indicates that at psychographic and decision-to-buy market share, majority of respondents agree that to wear muslim clothes is part of their lifestyle and they also agree that the models of clothes sold at Baitul Muslim As-Sidiq is suitable with modern lifestyle. It is reinforced by their willingness to allocate a few of their budget for buying muslim clothes. All respondents, whether males or females, agree that wearing muslim clothes is part of daâwah Islamiyyah. They also agree that wearing muslim clothes takes a part in maintaining the honor of themselves, their religion and their family. Furthermore, this research indicates that there is no significant difference in shopping muslim clothes and equipment between males and females according to psychographic market share. In the same time, there is no significant difference also in shopping muslim clothes and equipment between both categories according to benefit market share.